Indian women through the ages - Ghosh, S. K. (New Delhi, 1989)
This book highlight the problems faced by women, from pre-historic times to the present day, in all walks of life and covers all communities - Hindus, Muslim, Christians, Sikhs, Parsis and tribals who form the strength of our society.
Keywords: Women-India